2007
DOI: 10.1016/j.brainres.2006.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Event-related power modulations of brain activity preceding visually guided saccades

Abstract: To analyze the characteristics of the event-related desynchronization (ERD) and synchronization (ERS) of cortical rhythms during the preparation and execution of a lateralized eye movement, EEG was recorded in normal subjects during a visually guided task. Alpha and beta bands were investigated in three temporal intervals: a sensory period, a delay period and a saccade preparation period time locked with saccade onset. Modulations of ERD/ERS power, coupled with the task, reached the largest amplitudes over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 69 publications
(77 reference statements)
1
10
0
Order By: Relevance
“…A tentative hypothesis is that the bilateral representation of spatial attention for the right hemisphere cancelled out the tiny differences between electrophysiological activity preceding voluntary and reflexive saccades. Interestingly, a recent fMRI study [Petit et al, 2009] and studies examining power modulations in EEG alpha-band activity have observed similar asymmetries suggesting dominance of the right hemisphere in spatial processing [Brignani et al, 2007;Thut et al, 2006]. Since EEG-power modulations may serve as an index of attentional orienting to the left or right hemifield, examining the occurrence of such modulations prior to target onset might clarify the role of spontaneous attentional fluctuations in the control of voluntary and reflexive saccades.…”
Section: Discussionmentioning
confidence: 95%
“…A tentative hypothesis is that the bilateral representation of spatial attention for the right hemisphere cancelled out the tiny differences between electrophysiological activity preceding voluntary and reflexive saccades. Interestingly, a recent fMRI study [Petit et al, 2009] and studies examining power modulations in EEG alpha-band activity have observed similar asymmetries suggesting dominance of the right hemisphere in spatial processing [Brignani et al, 2007;Thut et al, 2006]. Since EEG-power modulations may serve as an index of attentional orienting to the left or right hemifield, examining the occurrence of such modulations prior to target onset might clarify the role of spontaneous attentional fluctuations in the control of voluntary and reflexive saccades.…”
Section: Discussionmentioning
confidence: 95%
“…In preparation for and during voluntary hand movements like button presses, the same pattern of beta band decrease followed by a rebound over contralateral motor areas is also reliably observed (e.g., Jasper and Penfield, 1949; Pfurtscheller, 1981). Likewise, several studies suggest that a decrease in beta band amplitude over contralateral posterior parietal areas accompanies the execution of saccades (e.g., Pesaran et al, 2002; Brignani et al, 2007; Carl et al, 2016). Moreover, Jo et al (2016) recently reported a negative correlation between the level of beta band amplitude over motor areas before initiating voluntary button presses and according RTs.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, spectral features of the qEEG in the alpha (8)(9)(10)(11)(12) band are sensitive to variations in perception, cognition or motor action [10,11]. The study of the alpha sub-bands, i.e., alpha 1 or slow-alpha (8-10 Hz) and alpha 2 or fast-alpha (10-12 Hz), has been shown to represent qualitative differences.…”
Section: Introductionmentioning
confidence: 93%
“…Several investigations have demonstrated that during tasks involving voluntary attention, the right hemisphere plays a role in the saccadic movements programming of both frontal eye fields [1], while the left hemisphere plays a role in the movement control of the contralateral side of our body [8,9]. In line with this, spectral features of the qEEG in the alpha (8)(9)(10)(11)(12) band are sensitive to variations in perception, cognition or motor action [10,11].…”
Section: Introductionmentioning
confidence: 94%